Stability of visual outcome between 2 and 5 years following corneal transplantation in the UK. Issue 1 (9th June 2017) - Chow, Sing-Pey; Hopkinson, Cathy L; Tole, Derek M; Jones, Mark N; Cook, Stuart D; John Armitage, W
Abstract : Background and Aims: Many studies of corneal transplantation focus on graft failure or rejection as endpoints, or report visual outcomes at one postoperative time point. We aimed to study the stability of visual outcomes between 2 and 5 years following corneal transplantation. Methods: All patients with keratoconus (868) or Fuchs endothelial dystrophy (FED) (569) receiving their first corneal transplant for visual purposes in the UK between January 2003 and December 2009 were included. The probability of visual improvement or deterioration (gain or loss of ≥2 Snellen lines, respectively) between 2 and 5 years after keratoplasty was modelled by multivariable logistic regression. Results: The majority of keratoconus patients with a penetrating keratoplasty (PK) or deep anterior lamellar keratoplasty maintained their visual acuity (651/868; 75%) while 15% (133/868) improved and 10% (84/868) deteriorated. Similarly, most patients with FED who received a PK maintained their vision (395/569; 70%) while 18% (105/569) improved and 12% (68/569) deteriorated.